CD200 expression in chronic lymphocytic leukaemia - Mannaru, Karissa Thamanna (My University, 2016)
Introduction: Chronic Lymphocytic Leukemia (CLL) is a small cell B cell neoplasm, demonstrating CD19/CD5 co-expression with a heterogeneous prognosis. Its distinction from Mantle Cell Leukemia/lymphoma (MCL) is necessary for accurate treatment strategy and prognostication. CD200 is a transmembrane antigen found on a range of haemopoietic cells, with a multifactorial immune-suppressive role. It is postulated to contribute to tumour biology by evading immune surveillance and enhancing immune tolerance. The differential expression of CD200 in CLL and MCL may be used as an immunophenotypic tool in separating these diagnoses. Its role as a prognostic and diagnostic marker is not established in the context of CLL in an African setting. Aims: To verify the value of CD200 in differentiating CLL from MCL during immunophenotypic assessment and to ascertain if its expression may be utilized as a prognostic marker in the context of CLL. Methods: Flow cytometric analysis of CD200 expression on normal lymphocytes and CD19/CD5 co-expressing B cell neoplasms was performed. A cut off value for identification of CD200 positivity was established. Statistical analysis of tumour expression of CD200 was then undertaken to determine its sensitivity and specificity as a diagnostic tool in CLL assessment. Established prognostic markers were collected for each case, for comparison to CD200 expression. Statistical analysis was used to establish the utility of CD200 expression as a surrogate prognostic marker. Results: CD200 is weakly positive on normal B-lymphocytes and negative on normal T lymphocytes. A cut-off mean fluorescence intensity of 20 was determined to constitute positivity for CD200 expression. Within the CD19/CD5 cohort obtained (n=57), 46/57 were identified as CLL and a further 7 as MCL. The sensitivity of CD200 was 97.8% with a specificity of 85.7%, with statistically significant positive and negative predictive value during immunophenotypic diagnosis of CLL. Requisition of laboratory prognostic markers was suboptimal in this cohort. There was no reliable association of CD200 expression with other markers of prognostic significance in this study. Conclusion: Within this small cohort, CD200 proved to be a sensitive marker for the discrimination of CLL from MCL during immunophenotypic analysis of CD19/CD5 co-expressing tumours. The role of CD200 as a prognostic tool in CLL could not be confirmed.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the Branch of Pathology (Haematology)